The impact of biologic therapies on extra-intestinal manifestations in inflammatory bowel disease: A multicenter study - Ferretti, Francesca; Monico, Maria Camilla; Cannatelli, Rosanna; Carmagnola, Stefania; Lenti, Marco Vincenzo; Di Sabatino, Antonio; Conforti, Francesco; Pastorelli, Luca; Caprioli, Flavio; Bezzio, Cristina; Saibeni, Simone; Mazza, Stefano; et al. (Frontiers in Medicine, 2022)
Introduction Patients with Inflammatory Bowel Disease [IBD] have a high risk of developing extra-intestinal manifestations [EIMs]. We aimed to assess the cumulative incidence and clinical course of EIMs in patients treated with Vedolizumab [VDZ] and non-gut selective biologic drugs. Materials and methods In this multicenter observational study, we enrolled 1182 IBD patients under biologic treatment in tertiary care centers, collecting the rate of new onset EIMs and the clinical course of new and pre-existing EIMs since the introduction of the ongoing biologic drug [259 VDZ versus 923 non-gut selective agents, median time 3 vs 4 years]. Results Among 1182 IBD patients [median age 46 years; 55% males] on biologics, the overall cumulative incidence of new onset EIMs was 4.1% [49/1182], in particular 6.6% [17/259] on VDZ vs 3.5% [32/923] on non-gut selective biologics [p = 0.02]. Amongst 224 patients reporting a new or pre-existing EIMs, those on VDZ showed a higher rate of clinical worsening compared to non-gut selective therapies [15.5% vs 7.3%, p = 0.08]. However, both showed a similar rate of modification of the therapeutic regimen. Female gender [HR 2.18], a longer course of the ongoing biologic therapy [HR 1.18], UC [HR 1.83] and VDZ therapy [HR 1.85] resulted to be significant risk factors of developing new EIMs. Discussion Our study suggests that the type of biologic treatment might affect the risk of developing EIMs, with a slightly higher risk in patients on gut-selective therapies. However, a similar clinical course is observed in the two groups.